Dangdut dan Rezim Orde Baru: Wacana Nasionalisasi Musik Dangdut Tahun 1990-an - Derta Arjaya (Lembaran Sejarah, 2016)
This research tries to answer two main questions. First, what was the reason for the nationalization of dangdut in 1990s period. Second, how was the discourse taken place and who benefited from the nationalization of the popular music. History method is applied in this research, by using sources, such as, magazines, newspapers, books, scientific works, which are spread in several places. The main inventions of this research are, firstly, the nationalization of dangdut was strongly related to the development of dangdut in the 1970’s to 1990’s periods. Secondly, the strategy of the regime to nationalize dangdut in the middle 1990s was conducted through supporting the development of positive dangdut. Third, the nationatization of dangdut in the 1990s benefited both the New Order regime and dangdut itself.